Self-medication practices with antibiotics among phase I MBBS students in a peripheral medical college of West Bengal - Lahiri, Surajit; Rituparna Maji; Sudip Ghosh; Chakraborty, Sohanjan (Asian Journal of Medical Sciences, 2023)
Background: Increased consumption of self-prescribed antibiotics may lead to resistance against them also causing rise in financial burden. Medical fraternity is in an advantageous position to use antibiotics of their choice. Aims and Objectives: The present study was conducted among medical undergraduates to estimate the prevalence and describe different attributes of self-medication among them. Materials and Methods: The study was conducted among 188 undergraduate students of MBBS phase 1 using complete enumeration method with the help of a predesigned pretested semi-structured self-administered questionnaire. Results: About 76.76% students were practicing self-medication and majority took it due to convenience (77.46%) and to get rid of fever, cough, and runny nose on the basis of previous doctor’s prescription (65.49%) mostly from community pharmacists (69.01%). About 43.66% students changed the antibiotics, 47.18% changed dosage and only 34.5% completed the course, 28.2% students had adverse reactions, and 36.6% students did not opine self-medication as an acceptable practice. Conclusion: Self-medication with antibiotics is a quite prevalent practice among the medical undergraduates of phase 1. Further studies will be helpful to assess the change of behavior among them during the progression through MBBS later on.